Evoked Compound Action Potentials to Guide Lead Placement: A Neuromonitoring Technique Case Series. (1st September 2019) - Falowski, Steven M
Abstract: INTRODUCTION: The procedure to place leads on the spinal cord traditionally required patients to be awake for reporting of device-induced paresthesias. Conversely, neuromonitoring using electromyography (EMG) recording determines optimal lead location while the patient is under general anesthesia. These techniques have been compared with regards to safety and efficacy, favoring the use of neuromonitoring1-2We present 7 subjects, incorporating the use of Evoked Compound Action Potential (ECAP) recording from implanted electrodes, using a new SCS system, and comparing the results with EMG recording. METHODS: Standard neuromonitoring protocols were employed at 2 institutions Once leads were implanted, stimulation current was increased until the following were observed: ECAP and EMG signal (late response [LR]), and EMG signal on the neuromonitoring EMG electrodes. An x-ray was obtained; postoperative paresthesia testing was performed to assess coverage obtained at different points along the implanted leads. RESULTS: Data were obtained from 7 patients, across 2 sites. Onset of EMG signals on implanted electrodes and EMG electrodes correlated. Furthermore, the ratio of current amplitude between EMG onset and ECAP onset (LR: ECAP), on implanted leads, provides a potential estimate of lead laterality and objective lead placement. Whereby a ratio <1 indicates leads are too lateral. This technique was used successfully to place leads under general anesthesia (1 case), without utilizing EMG recording as a dermatomal coverage marker. CONCLUSION: Intraoperative recording of ECAPs and EMG signals from implanted leads may facilitate optimized lead placement, without requiring additional equipment and setup. Analysis of ECAP morphology and its relationship with different waveforms could have diagnostic capabilities intraoperatively. This could be correlative with recent results showing the effect of different waveforms on EMG recording.